4D nanoimaging of Portland cement hydration. - Shirani, Shiva; Cuesta, Ana; Díaz, Ana; Trtik, Pavel; Holler, Mirko; Rack, Alexander; Lukic, Bratislav; Brun, Emmanuel; García-Aranda, Miguel Ángel (My University, 2024)
Portland cements are environmentally contentious, accounting for ≈8% of the anthropogenic CO2 emissions. The understanding of the cement hydration reactions (dissolution and precipitation processes) is important to contribute to develop cements with lower CO2 footprints. We are pushing 4D (3D+time) cement hydration nanoimaging within a multiscale framework. Full-field laboratory X-ray micro Computer Tomography (μCT) is widely used to study cement hydration but the best spatial resolution is about 2 μm for a Field of View (FoV) of ≈1×2 mm (H×V) with polychromatic measurements taking hours. Moreover, the contrast between the different components is poor. Full-field propagation-based phase-contrast synchrotron X-ray μCT can study similar FoVs ≈1×2 mm with better spatial resolution, ≈0.50 μm. The monochromatic measurements are fast, i.e. 5-10 minutes. Unfortunately, the contrast is only slightly better. Cement hydration can be studied with much better contrast and spatial resolution by scanning near-field ptychographic nano-computed tomography (nCT). In this case the FoV could be ≈200×30 μm with spatial resolution, close to 250 nm, and excellent component contrast. Even air and water can be differentiated. However, these nCTs takes about 3-4 hours in optimized beamlines (BL) at third generation synchrotrons. We will present here our latest 4D nanoimaging results (Shirani et al. (2023) Nature Comm. 14:2652) from data
Resumen de contribución al congreso "XI AUSE Conference and VI ALBA Users Meeting"
Keywords: Cemento Portland; Cristalografía por rayos; Sistemas de imágenes; Tomografía; X-ray imaging; Tomography; Nanoimaging; Synchrotron radiation